Evaluating the impact of a darts game intervention on cognitive function in older adults with and without mild cognitive impairment: a pilot study - Kawabata, Nami; Iida, Tadayuki; Kunishige, Masafumi; Fukuda, Hiroshi; Miyaguchi, Hideki; Harada, Toshihide (Frontiers in Rehabilitation Sciences, 2024)
Introduction The current study investigated the relationship between the characteristics of a darts game, including the throwing motion toward a target, and mild cognitive impairment (MCI). To this end, we examined the associations between cognitive function and mental health, and the shift in center of gravity while throwing darts. In a preliminary investigation, a 1-month dart game intervention was conducted among older individuals living in the community. The participants were divided into the non-MCI and MCI groups, and the relationship between center of gravity movement during throwing and the presence of dementia was examined. Methods The intervention lasted for 1 month and was tested on healthy older individuals (aged ≥ 65 years) recruited from the community. The Japanese version of the Montreal Cognitive Assessment and the Trail Making Test was used to assess cognitive function. Mental health was evaluated using the Kessler Psychological Distress Scale and the Subjective Well-being Inventory. The center of pressure was analyzed to determine the center of gravity shift during dart throwing. Results The analysis of factors influencing the determination of the MCI score during the intervention revealed a tendency for the center of gravity shift to be associated as a protective factor in the non-MCI group, although this association did not reach statistical significance (odds ratio = 0.942, p = 0.084). In the MCI group, a significant effect of age was observed in the MCI score (odds ratio = 1.539, p = 0.007). Conclusion The current findings suggest that conducting center of gravity shift testing could potentially provide a helpful tool for predicting early decline in cognitive function.